Growth Cone Tctp Is Dynamically Regulated by Guidance Cues - Gouveia Roque, Cláudio; Holt, Christine E. (Frontiers in Molecular Neuroscience, 2018)
Tctp contributes to retinal circuitry formation by promoting axon growth and guidance, but it remains unknown to what extent axonal Tctp specifically influences axon development programs. Various genome-wide profiling studies have ranked tctp transcripts among the most enriched in the axonal compartment of distinct neuronal populations, including embryonic retinal ganglion cells (RGCs), suggesting its expression can be regulated locally and that this may be important during development. Here, we report that growth cone Tctp levels change rapidly in response to Netrin-1 and Ephrin-A1, two guidance cues encountered by navigating RGC growth cones. This regulation is opposite in effect, as we observed protein synthesis- and mTORC1-dependent increases in growth cone Tctp levels after acute treatment with Netrin-1, but a decline upon exposure to Ephrin-A1, an inhibitor of mTORC1. Live imaging with translation reporters further showed that Netrin-1-induced synthesis of Tctp in growth cones is driven by a short 3’ untranslated region (3’UTR) tctp mRNA isoform. However, acute inhibition of de novo Tctp synthesis in axons did not perturb the advance of retinal projections through the optic tract in vivo, indicating that locally produced Tctp is not necessary for normal axon growth and guidance.